Технологии социального манипулирования в информационном обществе - Карпенко, Е. А. (ХНУРЕ, 2019)
The paper is considering the technologies of social manipulation in the modem information society. Entry into the global space in modem conditions occurs as a resuit of the use of information and communication technologies that exploit the nature of the unconscious person, which does not allow to ignore the topic of manipulation o f the mass consciousness